2009
DOI: 10.2174/1567270000906010025
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of a Diluted Prothrombin Time for Accurately Diagnosing Antiphospholipid Syndrome

Abstract: The usefulness of lupus anticoagulant (LA) and several antibodies for predicting thrombosis was assessed in patients with idiopathic thrombocytopenic purpura (ITP), systemic lupus erythematosus (SLE), lupus like disease (LLD), recurrent abortion and primary antiphospholipid syndrome (APS). LA was measured using the diluted Russell Viper Venom test (DRVVT) and the diluted prothrombin time (dPT).In healthy volunteers, the median (range) of the DRVVT and dPT ratio were 0.97 (0.88 -1.08) and 1.05 (0.85 -1.29), res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Alongside aPTT, the other PL-dependent routine coagulation screening test is the prothrombin time (PT), so perhaps inevitably, diluting the thromboplastin reagent has been employed to screen for LA, in the tissue thromboplastin inhibition test or dPT [56][57][58]. The use of a lower thromboplastin dilution, or undiluted reagent, operates as the confirmatory test.…”
Section: The Other La Assaysmentioning
confidence: 99%
“…Alongside aPTT, the other PL-dependent routine coagulation screening test is the prothrombin time (PT), so perhaps inevitably, diluting the thromboplastin reagent has been employed to screen for LA, in the tissue thromboplastin inhibition test or dPT [56][57][58]. The use of a lower thromboplastin dilution, or undiluted reagent, operates as the confirmatory test.…”
Section: The Other La Assaysmentioning
confidence: 99%
“…6 However, dPT is a widely performed, welldocumented, and sensitive screening test for LA when recombinant thromboplastin is used. [7][8][9][10] It has been reported that a considerable number of laboratories (50% of laboratories participating in the European Concerted Action on Thrombophilia Foundation) were using dPT beside the recommended tests for LA screening. 12,13 In previous studies, prolongation of the dPT was found to be associated with higher risk of thrombosis, 14 and receiver operating characteristic curve analysis indicated that the dPT ratio might be more useful for predicting thrombosis than diluted Russell viper venom time.…”
Section: Commentmentioning
confidence: 99%
“…12,13 In previous studies, prolongation of the dPT was found to be associated with higher risk of thrombosis, 14 and receiver operating characteristic curve analysis indicated that the dPT ratio might be more useful for predicting thrombosis than diluted Russell viper venom time. 10 Generally, a prothrombin-based assay performed with diluted thromboplastin has high sensitivity and specificity for the presence of LA, caused by both anti-b2GPI and anti-prothrombin antibodies. 8,15,16 According to the United Kingdom National Quality Assessment Scheme proficiency testing program, all the hemostasis laboratories that used the dPT as part of LA screening reported correct interpretation for all of the external quality control samples.…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation